Using multimedia resources in an online course with respect to students' learning preferences - Kišiček, Sanja; Garić, Ana; Lauc, Tomislava (2012)
In this paper we present a research on students’ learning styles and their learning preferences in a virtual learning environment within an online course. The content of the course is offered in the form of Moodle lessons containing three different types of multimedia resources: textual, pictorial resources accompanied by text and video resources. By analyzing the results of a VARK questionnaire, which label the students’ learning styles as visual, aural, read/write and kinesthetic, and matching them with the results of students’ feedback responses indicating what type of resources the students have been using, we determine on relationship between learning styles and preferences. Students with stressed visual learning style show lesser preferences towards usage of textual resources. Students with stressed read/write learning style show lesser preferences towards the usage of video resources. Understanding the learners’ preferences leads to more effective instructional design in an online learning environment.
Projekt MZOS
Projekt MZOS
ENG